Interpolation of Total Dissolved Solids (TDS) Concentration in A River Using Ordinary Kriging Method - Sri Wahyuningsih; Idah Andriyani; Dian Purbasari; Trioda Rizqi Nurcahyo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Water quality is a key indicator related to the sustainability of living things in a watershed. However, human activities have led to a decline in the water quality caused by industrial, domestic and agricultural waste. This study aims to predict the pattern of TDS parameters at unsampled points through a geostatistical approach, namely Kriging. Experimental measuements were conducted in the Bedadung River, Jember Regency, especially in a segment of Patrang to Wuluhan sub-districts. Currently, the river is classified as Class 3, which is below the standard, one of the water quality parameters is TDS (Total Dissolved Solid). The TDS estimation results were obtained in the range of 48.26 mg/L - 175.52 mg/L. The predicted value of TDS using the kriging method at unsampled points resulted in an RRMSE value of 8.40 %. This study revealed that the water quality of Bedadung River from Patrang to Wuluhan sub-districts was still below Class 2 standards, emphasizing the need for continuous monitoring and improvement efforts. Keywords: Ordinary kriging, River water quality, Semivariogram, Total dissolved solid.